Manajemen Pendidikan dalam Perspektif Al-Qur’an dan Hadis - Sangadah, Siti; Sriyanta, Sriyanta; Anshory, Muhammad Isa (TSAQOFAH, 2025)
This study discusses educational management from the perspective of the Qur'an and Hadith. Education is highly valued in Islam. By citing the verses of the Qur'an and the Hadith of the Prophet as a guide, we can see how the principles of educational management can be applied in the world of Islamic education. A descriptive-analytical qualitative approach is used in this study by examining the texts of the Qur'an, Hadith, and related literature. This study examines key concepts such as leadership, learning, and personal development in the context of Islamic education and explains how these principles can be useful for educators and school administrators. The results of this study by understanding and applying the teachings of the Qur'an and Hadith in educational management, we can create a better educational environment that is in line with Islamic values, so that we can achieve the noble ultimate goal of educating a generation that is pious and has good morals.